PENGGUNAAN PINTEREST SEBAGAI MEDIA DESAIN BUSANA UNTUK MENINGKATKAN PEMBELAJARAN MAHASISWA DESAIN FASHION - Pandansari, Purwosiwi; Purwanti, Rina; Kustiyono, Kustiyoni; Jalil, Abdul; Lathifah, Lathifah (Lembaga Pendidikan dan Penelitian Manggala Institute, 2024)
This research article examines the use of pinterest applications as a fashion design teaching material in students of Vocational Education Fashion Design. The aim is to describe the effectiveness of pinterest applications in improving fashion design skills that will be displayed into a real fashion product. Pinterest, as an application engine that finds visual ideas to inspire styles, hobbies, recipes, eating styles and many more ideas that will come up to suit the inspiration you are looking for. This research uses a type of quantitative research with a descriptive approach. Research results show that pinterest is effective as a learning medium, improving skills, understanding, developing ideas and creators of a product that will be made by students of vocational education fashion design.The integration of digital technologies such as the pinteres application provides learning experiences and prepares students to become designers. It is suggested that the pinterest application can be used more widely in various learning to improve the quality of education. The use of the pinterest application provides a positive and worthwhile feature to use.